2018
DOI: 10.1002/pi.5619
|View full text |Cite
|
Sign up to set email alerts
|

Properties of bismaleimide resin modified with polyrotaxane as a stress relaxation material

Abstract: In this study, 4,4′‐diphenylmethane bismaleimide (BMI)/2,2′‐diallylbisphenol A (DABPA) resin was modified with polyrotaxane (PR) as a stress relaxation material. Based on a dynamic mechanical analysis and various properties of the cured resin, the influence of the motion of PR on the cured properties of BMI/DABPA/PR alloy is discussed. The cyclic molecule α‐cyclodextrin (α‐CD) that is threaded onto the PR axis contains a methacryl group in its side chain that reacts with the allyl group of BMI/DABPA resin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In our previous study, we modified BMI/DABPA resin with PR having methacryl groups at the ends of the side chains and reported its dynamic viscoelastic behavior 20 . The BMI/DABPA/PR alloy was found to form a homogeneous structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we modified BMI/DABPA resin with PR having methacryl groups at the ends of the side chains and reported its dynamic viscoelastic behavior 20 . The BMI/DABPA/PR alloy was found to form a homogeneous structure.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that when BMI/DABPA resin was modified with PR having methacryl groups on the side chain, the methacryl groups reacted with the allyl groups of DABPA to form a BMI/DABPA/PR alloy with a homogeneous structure 20 . Modification of BMI/DABPA resin with PR increased the glass transition temperature compared to that of BMI/DABPA resin because of the formation of a denser crosslink network structure than that of the unmodified resin.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, TGA and DMA were conducted to investigate the thermal stability and glass transition temperatures of the blends, respectively 48,49 . Figure 8A, B shows the TGA curves and DTG curves of neat DABP/BDM system and PPENS‐DA/DABP/BDM system, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, polyrotaxanes (PRs), as a strength enhancement material, composed of multiple host molecules threaded on a polymer chain with bulky end-caps have drawn much attention . For example, PR initially developed by Harada and coworkers using poly­(ethylene glycol) (PEG) and α-cyclodextrin (α-CD) has been used as a cross-linker to effectively improve the mechanical properties of hydrogels .…”
Section: Introductionmentioning
confidence: 99%
“…8 In recent years, polyrotaxanes (PRs), as a strength enhancement material, composed of multiple host molecules threaded on a polymer chain with bulky end-caps have drawn much attention. 9 For example, PR initially developed by Harada and coworkers using poly(ethylene glycol) (PEG) and α-cyclodextrin (α-CD) has been used as a cross-linker to effectively improve the mechanical properties of hydrogels. 10 When an external force distorts the shape of materials crosslinked by PR, the stress focused on a portion of the polymer network can be effectively relieved by the sliding motion of α-CDs on the PEG chain in PRs.…”
Section: Introductionmentioning
confidence: 99%